Chronic high-fat diet impairs collecting lymphatic vessel function in mice. - Katrin S Blum; Sinem Karaman; Steven T Proulx; Alexandra M Ochsenbein; Paola Luciani; Jean-Christophe Leroux; Christian Wolfrum; Michael Detmar (PLoS ONE)
Lymphatic vessels play an essential role in intestinal lipid uptake, and impairment of lymphatic vessel function leads to enhanced adipose tissue accumulation in patients with lymphedema and in genetic mouse models of lymphatic dysfunction. However, the effects of obesity on lymphatic function have been poorly studied. We investigated if and how adipose tissue accumulation influences lymphatic function. Using a lymphatic specific tracer, we performed in vivo near-infrared (NIR) imaging to assess the function of collecting lymphatic vessels in mice fed normal chow or high-fat diet (HFD). Histological and whole mount analyses were performed to investigate the morphological changes in initial and the collecting lymphatic vessels. HFD was associated with impaired collecting lymphatic vessel function, as evidenced by reduced frequency of contractions and diminished response to mechanostimulation. Moreover, we found a significant negative correlation between collecting lymphatic vessel function and body weight. Whole mount analyses showed an enlargement of contractile collecting lymphatic vessels of the hind limb. In K14-VEGF-C mice, HFD resulted in a reduced spreading of the tracer within dermal lymphatic vessels. These findings indicate that adipose tissue expansion due to HFD leads to a functional impairment of the lymphatic vasculature, predominantly in collecting lymphatic vessels.